2021
DOI: 10.3390/molecules26154469
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Effect of Colonic Fermented Phenolic Compounds from Jaboticaba (Myrciaria trunciflora) Fruit Peel in a 3D Cell Model of Colorectal Cancer

Abstract: Jaboticaba is a Brazilian native berry described as a rich source of phenolic compounds (PC) with health promoting effects. PC from jaboticaba peel powder (JPP) have low intestinal bio-accessibility and are catabolized by gut microbiota. However, the biological implication of PC-derived metabolites produced during JPP digestion remains unclear. This study aimed to evaluate the antiproliferative effects of colonic fermented JPP (FJPP) in a 3D model of colorectal cancer (CRC) composed by HT29 spheroids. JPP samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…Plant-derived bioactive compounds, including certain phenolic derivatives and bioactive peptides, have been shown to modulate the composition of the intestinal microbiota (inhibiting the population of pathogens and promoting the growth of beneficial bacteria). They also prevent the production of toxic compounds such as LPS, hydrogen sulfide and indole and increase the production of beneficial metabolites such as SCFA and other bioactive compounds that target multiple pathways and tissues, resulting in improved intestinal health, glycemic and lipid control and inflation [ 25 , 26 ]. Regarding the relationship between the bioaccesibility and bioactivity of plant bioactive compounds such as polyphenols and the action of the human microbiota, it is important to consider that only a proportion of the daily amount of bioactive compounds ingested is absorbed or metabolized by certain bacterial strains.…”
Section: Discussionmentioning
confidence: 99%
“…Plant-derived bioactive compounds, including certain phenolic derivatives and bioactive peptides, have been shown to modulate the composition of the intestinal microbiota (inhibiting the population of pathogens and promoting the growth of beneficial bacteria). They also prevent the production of toxic compounds such as LPS, hydrogen sulfide and indole and increase the production of beneficial metabolites such as SCFA and other bioactive compounds that target multiple pathways and tissues, resulting in improved intestinal health, glycemic and lipid control and inflation [ 25 , 26 ]. Regarding the relationship between the bioaccesibility and bioactivity of plant bioactive compounds such as polyphenols and the action of the human microbiota, it is important to consider that only a proportion of the daily amount of bioactive compounds ingested is absorbed or metabolized by certain bacterial strains.…”
Section: Discussionmentioning
confidence: 99%
“…TPs may inhibit CRC metastasis by inhibiting matrix metalloproteinase-9, which is closely associated with tumor metastasis and plays an important role in the infiltration of tumor cells (Mileo et al, 2019). Augusti et al (2021) presented the chemopreventive effect of jaboticaba peel powder in terms of reducing inflammation and CRC cell proliferation in a complex 3D model of CRC for the first time. Jaboticaba peel powder contains phytochemicals extracted from jaboticaba fruit peel, which are fermented by flora in the intestine to form phenolic compounds.…”
Section: Phenolicsmentioning
confidence: 99%
“…Colorful fruits, vegetables, flowers, and grains contain water-soluble pigments known as anthocyanins, which have shown bioactive properties in a number of ways. As dietary supplements, anthocyanins provide a wide range of health benefits, for example, antioxidant, antimicrobial, anti-inflammatory, and neuroprotective. The retrieval has already found that with the increasing number of publications, the renewed public interest of anthocyanins research is continuing, particularly in intestinal diseases. ,, …”
Section: Introductionmentioning
confidence: 99%